2008
DOI: 10.1007/s11172-008-0256-8
|View full text |Cite
|
Sign up to set email alerts
|

Photophysical and electrochemical properties of the outer-sphere associate of [Ru(bipy)3]2+ with p-sulfonatothiacalix[4]arene

Abstract: 1 H NMR titration and X ray diffraction analysis revealed that [Ru(bipy) 3 ] 2+ forms an outer sphere inclusion complex with p sulfonatothiacalix[4]arene in a ratio of 1 : 1 in both aqueous solutions and the solid state. According to cyclic voltammograms and fluorimetric data, the outer sphere association of [Ru(bipy) 3 ] 2+ with p sulfonatothiacalix[4]arene changes the reversible character of the electrochemical oxidation of [Ru(bipy) 3 ] 2+ and lowers its emission intensity.Polypyridyl complexes of ruthenium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Calixarene electro-switchable host-guest systems described in literature [37][38][39][40][41][42][43] operate through the reversible redox switching of guests. Our results obtained previously [53] and in this investigation demonstrate the possibility of creating switchable systems with the redox-conversion of calixarene containing redox-active groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Calixarene electro-switchable host-guest systems described in literature [37][38][39][40][41][42][43] operate through the reversible redox switching of guests. Our results obtained previously [53] and in this investigation demonstrate the possibility of creating switchable systems with the redox-conversion of calixarene containing redox-active groups.…”
Section: Resultsmentioning
confidence: 99%
“…(Thia)calix[n]arenas and calix [4] resorcines, as macrocyclic polyphenols, are electrochemically active compounds with a tendency for oxidation [37][38][39][40][41][42][43]. But these oxidation reactions are reversible only under specific conditions, and in most cases they are irreversible.…”
Section: Introductionmentioning
confidence: 99%
“…This decrease does not result from Yb(III), because p -sulfonatothiacalix[4]arene itself provides the same quenching. The quenching of [Ru(dipy) 3 ] 2+ emission by p -sulfonatocalix[4]arene and p -sulfonatothiacalix[4]arene was discussed in more detail in ref . The obtained data indicate the lack of Ru−Yb energy transfer and the quenching effect of [Ru(dipy) 3 ] 2+ on Yb(III)-centered luminescence of [YbHL] 4− in aqueous solutions resulting from their ion pairing.…”
Section: Resultsmentioning
confidence: 99%
“…85 Perching binding is known in previous cases where the macrocycle cavity is constricted, although the individual interactions are noticeably different. [86][87][88][89][90] Since we have previously shown that redox interconversions of alcohols and ketones correspond in logic terms to a Reset-Set ip-op, 85 the two different modes of inclusive binding with trialcohol 2 and perching binding with triketone 1 can be represented as outputs in this situation (Fig. 3A).…”
Section: Resultsmentioning
confidence: 99%